A wearable and high-performance capacitive pressure sensor based on a biocompatible PVP nanofiber membrane via electrospinning and UV treatment. Issue 29 (27th June 2022) - Ren, Mengna; Li, Jiamin; Lv, Luyu; Zhang, Mengqi; Yang, Xiaojun; Zhou, Qihui; Wang, Danyang; Dhakal, Rajendra; Yao, Zhao; Li, Yuanyue; Kim, Nam Young
Abstract : We report the fabrication, superior performance and applications of a flexible capacitive pressure sensor based on a biocompatible polyvinyl pyrrolidone nanofiber membrane, prepared by electrospinning and ultra-violet photochemical after treatment. Abstract : In recent years, flexible pressure sensors have become an important part of soft electronics due to their tactile sensing abilities. However, manufacturing pressure sensors with high sensing performance and excellent applicability is still a great challenge. In this paper, we report the fabrication, sensing performance and applications of a flexible capacitive pressure sensor based on a polyvinyl pyrrolidone (PVP) nanofiber membrane (NM), which has a better biocompatibility and a wider applicability than the traditional dielectric layer materials. The cost-effective process of electrospinning and an ultra-violet (UV) photochemical aftertreatment are employed to prepare a PVP NM, which contribute to improving the performance of the sensor. The experimental results show that our sensor exhibits a fast response/recovery time (41/36 ms), a high sensitivity (0.278 kPa −1 at 0–2 kPa), a wide pressure range (0–200 kPa), an ultra-low detection limit (∼50 Pa) and an excellent stability (8000 cycles). Thanks to its superior performance, the sensor can be used to monitor various subtle physiological and physical signals, such as pulse rate, respiration, mouse clicks, body movement and air flow. In addition, a 4 × 4 sensor array is fabricated that can map objects with various geometries, which demonstrates its ability to accurately identify the spatial pressure distribution. The developed high-performance and wide-applicative flexible sensor can provide new opportunities for innovative applications of advanced human–computer interface systems.